Preparation and characterization of poly(MMA-CO-EGDMA-CO-VBC) via photoinitiated dispersion polymerization route to sulfonated hypercrosslinked resin - Rabiatuladawiah, Mahmod (2018)
A sulfonated hypercrosslinked polymer resin was derived from poly(MMA-co-EGDMA-co-VBC) polymer. In the present study, the sulfonated hypercrosslinkedpolymer resin was synthesized via two stages; photoinitiated dispersion polymerization employed to synthesis polymer precursor and post-polymerization which involved hypercrosslinking reaction and functionalization reaction to obtained sulfonated resin. In the first stage (photoinitiated dispersion polymerization) was conducted to counter the problems regarding the method of conventional dispersion polymerization in terms of the disturbance of functional reagents during nucleation stage. In this stage, which was the preliminary stage of the study, several parameters had been investigated: types of monomer, types of photoinitiators (PI), reaction times, and the amount of crosslinker, co-monomer, stabilizer as well as solvent/porogen ratio. In a screening test using a full factorial design of experiment (DoE), a 24 full factorial design was used to determine the significant parameters that could affect the yield of polymer precursor obtained in terms of the amounts of crosslinker, co-monomer, PI and also reaction times. The DoE analysis showed that the most significant factor was the reaction times. For further optimization study, central composite design (CCD) approach were design using the factor the amounts of crosslinker, co-monomer and PI were chosen as parameters in order to obtain high yield and good quality of polymer precursor. In the second stage (post-polymerization), the optimized precursor underwent two approaches which is hypercrosslinking reaction was conducted first before functionalization reaction and second approach hypercrosslinking reaction conducted after functionalization. Both approaches were conducted to overcome the low specific surface area (SSA) of sulfonated resin. The characterizations involved were the scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray fluorescence (XRF), CHNS analysis, Brunauer-Emmet-Teller (BET) analysis, particle size distribution (PSD) and thermal gravimetric analysis (TGA) in both stages meanwhile ion exchange capacity (IEC) value, specific surface area, morphology and thermal stability involved in the post-polymerization. In conclusion, the present study has provided significant guidelines and basic understanding of the synthesized sulfonated hypercrosslinked polymer resin derived from poly(MMA-co-EGDMA-co-VBC) polymer. It was found that first approach in post-polymerization resulting higher SSA and IEC value compared to second approach.